Study of the Mechanism of Chromium Removal in Tannary Effluent by Electrocoagulation Through Zeta Potential Measurements - Zaroual, Z.; Azzi, M.; Chainet, E.; Karhat, Y. (International Journal of Engineering and Technology, 2019)
The main objective of this paper is to discuss the behavior of the flocs formed during chromium (III) removal tests by electrocoagulation with iron electrode, through zeta potential measurements. The potential zeta is measured on chromium synthetic solutions and on the real tannery effluent previously treated by electrocoagulation. The effects of operating parameters such as time, potential electrolysis and pH on the zeta potential have been investigated. The obtained results show two different behaviors of the flocs in real tannery effluent and chromium synthetic solutions. Furthermore, the mechanism of electrocoagulation is elucidated.Â Â